Constructing technology of a meteor-burst communication system with code division multiplexing - Holovan, O.; Kharchenko, V. (Radiofizika i èlektronika, 2020)
Subject and Purpose. The paper presents a technology of constructing a promising meteor-burst communication system (MBCS) with code division multiplexing. It increases the bandwidth and improves the noise immunity and covert operation of the system. Methods and Methodology. The proposed technology is based on software-defined radio (SDR) and provides MBCS adaptation to the environment conditions by means of software parameter control of the signals and their transfer protocols. It includes a technique of forming a large ensemble of signals with a direct sequence spread spectrum and improved auto- and cross-correlation properties, involves the optimal reception and matched digital filtering of large-base signals. In order to improve the noise immunity, the narrow-band interference rejection in the signal spectrum is proposed and is jointly software installed with the matched filtering. The detection and synchronization techniques effectively working in the non-Gaussian and non-stationary interference conditions gained consideration. Results. A method of forming a large ensemble of direct sequence spread spectrum signals with improved auto- and cross-correlation properties has been software implemented using a pseudorandom permutation of codeword elements of a maximum-length register code. Designed with the use of fast Fourier transforms, algorithms of digital matched filtering and interference rejection as applied to large-base signals have been implemented via field-programmable gate arrays (FPGA). A method of detection and synchronization of large-base signals has been proposed and software implemented on the FPGA basis. Conclusion. The proposed algorithms and their implementation methods make it possible to increase the bandwidth, improve noise immunity and enhance covert operation of the meteor-burst communication system with code division multiplexing.